2022
DOI: 10.3389/fneur.2021.799222
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Dysbiosis in Acute Ischemic Stroke Associated With 3-Month Unfavorable Outcome

Abstract: BackgroundAlterations in the gut microbiota after ischemic stroke have been demonstrated, whereas the effect on stroke outcome remains to be established.MethodsA total of 132 consecutive patients with acute ischemic stroke were prospectively enrolled. Their gut microbiomes within 24 h of admission were profiled using 16S ribosomal RNA (rRNA) gene (V3–V4 region) sequencing. Microbiota comparisons were made between groups with good outcome (n = 105) and poor outcome (n = 27) based on 3-month modified Rankin Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…While this inflammatory shift can help to mitigate the acute effects of stroke in the brain, the residual inflammation in the weeks and months following the stroke is likely undermining recovery. Previous studies have also found that butyrate-producing bacteria were significantly reduced in cerebral ischemia patients and that this reduction is associated with poor outcomes (27,88,89). Future studies should explore treatments targeting the composition of microbial communities following stroke as a way to boost recovery from stroke in combination with other rehabilitation therapies.…”
Section: Discussionmentioning
confidence: 93%
“…While this inflammatory shift can help to mitigate the acute effects of stroke in the brain, the residual inflammation in the weeks and months following the stroke is likely undermining recovery. Previous studies have also found that butyrate-producing bacteria were significantly reduced in cerebral ischemia patients and that this reduction is associated with poor outcomes (27,88,89). Future studies should explore treatments targeting the composition of microbial communities following stroke as a way to boost recovery from stroke in combination with other rehabilitation therapies.…”
Section: Discussionmentioning
confidence: 93%
“…Consequently, it appears that beta gut microbiota diversity may provide more information regarding the gut microbiota-stroke link in addition to alpha gut microbiota[ 16 ].…”
Section: To the Editormentioning
confidence: 99%
“… 199 Those with poor post-stroke outcomes were found to have the same three major changes in gut microbiome composition but to a greater extent. 203 Understanding this phenomenon is important, as gut dysbiosis has been associated with diminished survival. Spychala et al used stroke mice models to show that aged mice or those with aged gut microbiota had an elevated Firmicutes to Bacteroidetes (F:B) ratio which was associated with lessened survival and post-stroke recovery.…”
Section: Strokementioning
confidence: 99%
“…The degree of stroke‐related gut dysbiosis has also been shown to be strongly and positively associated with stroke severity based on the National Institute of Health Stroke Score and post‐stroke disability based on the Modified Rankin Scale 199 . Those with poor post‐stroke outcomes were found to have the same three major changes in gut microbiome composition but to a greater extent 203 . Understanding this phenomenon is important, as gut dysbiosis has been associated with diminished survival.…”
Section: Strokementioning
confidence: 99%